Case Report: Treatment of Extremely Preterm Infants With Birthweight Below 300 g: Case Series - Yoshihiko Shitara; Satsuki Kakiuchi; Takeo Mukai; Kohei Kashima; Motohiro Kato; Naoto Takahashi (Frontiers Media S.A., 2021)
Reports on the birth of infants weighing <300 g are quite rare and little is known about the best practices in treating such micropreemies. Therefore, we report here on three cases of low birthweight infants weighing <300 g, of whom two infants survived. The birthweights and gestational ages were ranging 279-293 g and 22 + 6/7 - 23 + 6/7 weeks, respectively. All the infants had severe fetal growth restriction and prematurity. The infant in case 1 died of hepatic rupture, perhaps due to birth trauma, which emphasized the need for less invasive obstetric procedures including en caul delivery. The infant in case 2 managed to survive through severe prematurity secondary to hydrops fetalis. However, complications followed soon as tracheal granulation tissue was formed with neurodevelopmental impairment. The infant in case 3 was born recently and her clinical course was less remarkable without severe complications, despite having the least gestational age and birthweight among the three patients. The improved care protocols for extremely low birthweight infants over these years through experiential learning including that with cases 1 and 2 may have ensured the better outcome of case 3. Accumulating evidence and recording the experience of such cases with continuous constructive discussion can contribute to better outcomes and appropriate parental counseling for extremely small babies in the future.